SPIES Training Model to Improve Teacher’s Competence in 21st Century Learning - Pramono, Margareta Hani; Ismanto, Bambang; Satyawati, Sophia Tri (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The SPIES training model in Collaborative Learning materials serves as a tool to improve teacher competency in 21st-century learning. This training syntax helps teachers understand Collaborative Learning concepts and practices. This study aims to produce a more collaborative training syntax called the SPIES training model and improve teacher teaching competence. This type of research is development research. This R&D applies the Borg and Gall model, which is integrated with the Dick and Carrey training model. Data was collected by distributing questionnaires, in-depth interviews, pre-test, and post-tests. The subjects of this study were 15 teachers from three private schools. Experts who validate the design and materials ensure the training model and material feasibility. The data analysis included testing the validity and reliability of the instruments used. The normality distribution test and paired t-test were carried out to examine the effect of training. The results of this study are that the SPIES training model has been validated by experts with a feasibility level of 88.24% (very feasible). The material feasibility check percentage is 91.67% (very possible). The t-test results show that the post-test is different from the pre-test. The SPIES training model is effective for increasing teacher competency in 21st-century learning. It was concluded that the SPIES training model is feasible for improving teacher competency.